A NEW AND EFFICIENT PROPOSITION TO FIND AN INITIAL BASIC FEASIBLE SOLUTION OF TRANSPORTATION PROBLEM (International Journal of Food and Nutritional Sciences, 2022)
Transportation problem (TP) is mostly related to find the total transportation cost(TC) that minimization through an optimal solution. An initial basic feasible solution (IBFS) isto find out the optimal solution. In this paper a new method to find an initial basic feasiblesolution of transportation problem. This method is illustrated with some numerical examplesusing proposition.